T70. IDENTIFYING YOUTH AT CLINICAL HIGH RISK: WHAT'S THE EMOTIONAL IMPACT?. (9th April 2019) - Woodberry, Kristen; Powers, Kate; Bryant, Caitlin; Downing, Donna; Verdi, Mary; Kennedy, Leda; Shapiro, Daniel; Girgis, Ragy; Brucato, Gary; Huang, Debbie; Crump, Francesca; Corcoran, Cheryl; et al.
Abstract: Background: In spite of advances in early intervention in major mental illness, concerns linger regarding the risks of identifying youth as at clinical high risk (CHR) for psychosis. In particular, stigma in this population has been associated with increased emotional distress, social withdrawal, non-engagement in treatment, and suicide risk. Being told one has a CHR syndrome may be one source of stigma, yet no prior studies have conducted assessments both before and after people are given this feedback. Within the context of a larger study of stigma, we compared emotional responses to the CHR concept assessed before and after feedback by study clinicians. Notably, some participants had been already told of their risk prior to study entry whereas others had not. We expected different reactions to study feedback in these two groups. An informed discussion of risk might reduce stigma in those already worried about psychosis whereas it might increase stigma for those considering their risk for the first time. Thus, we predicted a small decrease in negative emotions following feedback in the first group, a small increase in the second, and no significant change in negative emotions for the group as a whole. Methods: Fifty-seven CHR participants ages 12–35 were interviewed both before and after receiving formal clinical feedback about their risk status and eligibility for the study. This feedback typically included elements of psychoeducation and information about treatment options. In each interview participants were asked 1) the degree to which they felt 12 emotions in relation to risk for psychosis or schizophrenia, 2) whether they thought it was better to not tell anyone about psychosis risk. We analyzed pre-post change using general linear modeling with group (those told before study entry and those first told in the study context) as a between-subjects variable and the time between pre and post interviews as a covariate. Results: Stigma was a significant concern in this sample as the vast majority of participants endorsed "It is better that I not tell people that I am at-risk, " both before and after feedback (75% pre to 71% post, McNemar test, p = 0.75). However, contrary to our hypothesis, participants experienced a significant decline in negative emotions (embarrassed, different, angry, ashamed, sad, worried; F= 20.7, p <0.001) post- vs. pre-feedback, even controlling for the significant effects of time (M = 16 days between assessments; F= 3.7, p =0.033). This was true for those who reported already having been told that they were at risk for psychosis (N = 35; F = 20.0, p < 0.001) as well as for those who were first told they were at risk in the context of the study (F =4.0, p = 0.038). Strikingly, a third of this latter group continued to report not having been told they were at risk even immediately after feedback. Additionally, in the larger group, ten believed that they already had schizophrenia and two maintained this belief even after being told that they did not. Discussion: This is the first study to assess emotional aspects of stigma in CHR youth both before and after formal feedback about their psychosis risk. In contrast to concerns, feedback provided in the context of specialized early psychosis programs may actually reduce distress in these youth. The fact that the number of days between assessments did not fully account for the significant changes in negative emotions suggests that these changes were unlikely to be due to time alone. Importantly, participants' varied impressions of what they had been told or whether they were at risk suggest that feedback is not the only factor influencing self-identification and stigma.